Lavish grater / Maisara Zainalabidin … [et al.] - Zainalabidin, Maisara; Sazoli, Nur Ayu Syahira; Abdul Ghani, Nur Izzati Hidayah; Hamzah, Nurul Hamizah; Wei Loon, Koe (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The cooking process can make more easier when the kitchen utensils more convenient. The main problem that rarely happen when there is not enough space to put the utensils in the kitchen. The idea had chosen through fair voting. The lavish grater is an innovation product with combination of defrosting tray and has a drawer that comes with slicing tools. The design of the product highlights the quality of two product which for the defrosting tray made with from a special alloy with thermal conductivity and no electricity needed when to use. For the slicing tools, it comes with the quality blade and easy to slicing the vegetables when waiting the meat defrost.